INNOVATIVE APPROACHES TO MANAGING MARKETING STRATEGIES IN TOURISM COMPANIES: AN ANALYSIS OF UZBEKISTAN AND INTERNATIONAL EXPERIENCE - Gulsanamkhon A. Boykuzieva; Aziza A. Kadirbaeva (Ecominds Press, 2026)
This article examines innovative approaches to managing marketing strategies in tourism companies, with a particular focus on both international practices and the evolving tourism market of Uzbekistan. Global experience in the application of digital systems, artificial intelligence, virtual and augmented reality technologies, influencer marketing, and sustainable tourism branding is analysed to identify key trends shaping contemporary tourism marketing. The study provides a comparative assessment of the Uzbek tourism market against international benchmarks and highlights advanced marketing approaches aimed at improving competitiveness and market visibility. The findings suggest that the digitalisation of marketing processes, expansion of personalised tourism services, and effective use of modern communication tools can significantly enhance marketing performance. Adoption of these innovative strategies has the potential to strengthen the competitiveness of Uzbekistan’s tourism industry and support its integration into the global tourism market.
Keywords: Tourism; marketing strategy; innovative approaches; digital ecosystem; artificial intelligence; VR/AR technologies; influencer marketing; branding.